Melchior Wańkowicz in the Warsaw-Based “Rój” and the New York-Based “Roy”. The Image of the Writer Based on Materials from the Roy Publishers Archive - Krupa, Barbara (Porównania, 2025)
Melchior Wańkowicz was not only a writer and a talented reporter, but also a publisher. He created a thriving company and, together with Marian Kister, made it one of the most prolific publishing houses in interwar Warsaw. It was especially known for publishing literary stars of the period, including Julian Tuwim, Tadeusz Boy-Żeleński, Witold Gombrowicz, Tadeusz Dołęga-Mostowicz, Pola Gojawiczyńska, Czesław Centkiewicz, Karol Irzykowski, Antoni Słonimski, Jan Lechoń, Józef Wittlin and Bruno Schulz. “Rój” was the first to publish works by European and American authors such as Thomas Mann, Sigrid Undset, James Joyce, Marcel Proust, Franz Kafka, Bertrand Russel, Ernest Hemingway and many others. In 1940, the publishing house moved to New York and began operating as Roy Publishers. Wańkowicz chose not to continue the publishing work with the Kisters. The article analyzes the mutual relationship between the Kisters and Wańkowicz, the involvement of Roy Publishers in New York in the publication of Wańkowicz’s books, and the writer’s multifaceted promotion within the Polish communities in North America and Western Europe. The research is based on the Roy Publishers Archive collection, previously unknown to researchers, housed in the Special Collections at the H. Green Library at Stanford University in California, USA. The collection, purchased in 2015, was not organized, compiled and made available to users until 2022. Undoubtedly, the materials in the collection shed new light on the roles of the publishing house’s associates and its activities on both continents.